Pengembangan Kualitas Sumber Daya Manusia Sekolah Dasar 46 Banda Aceh - Bararah, Isnawardatul (Intelektualita: Journal of Education Sciences and Teacher Training, 2024)
This study aims to analyze the Development of Human Resource Quality at SD 46 Banda Aceh. This study uses a qualitative descriptive approach, data was collected through in-depth interviews with school principals and non-participant observation. The results of the study indicate that human resource Development at SD 46 Banda Aceh can be carried out effectively through an inservice training program that is integrated with the specific needs of teachers and staff. schools can improve the quality of education and prepare future generations to face global challenges. Also carried out through four steps (1) needs analysis, (2) compiling a development program, implementing training, evaluating the program and follow-up.